Psychological distress in young adults with well-controlled psoriasis - Merzel Šabović, Eva Klara; Kraner Šumenjak, Tadeja; Janić, Miodrag (Frontiers in Psychiatry, 2026)
IntroductionPsychological distress is common in psoriasis, but its prevalence and possible biological correlates in young adults with well-controlled disease remain unclear. In this study, we aimed to assess the presence of anxiety and depressive symptoms in young, well-treated psoriasis patients, who were primarily expected to have no or minimal psychological distress, and to explore potential associations with inflammatory and metabolic markers.MethodsIn a cross-sectional cohort of 80 psoriasis patients (women/male: 45/35; mean age 38.7 ± 4.2 years) psychological symptoms were assessed using the Hospital Anxiety and Depression Scale (HADS), with HADS-A and HADS-D subscales evaluating anxiety and depression symptoms. Exploratory associations with inflammatory cytokines and metabolic indices were examined using regression analyses and random forest machine-learning models.ResultsAnxiety symptoms were identified only in 5 patients (women/male: 4/1; 6%), and depressive symptoms in 10 patients (women/male: 6/4; 12%). Affected individuals had clinically significant anxiety (HADS-A: 12/21) and borderline depressive symptoms (HADS-D: 10/21). No significant associations between HADS scores and inflammatory or metabolic markers were found. Exploratory random forest models tentatively identified IL-6, IL-23, FIB-4, HOMA-IR, and waist circumference as the strongest contributors to variance in depressive symptoms, while no clear contributors emerged for anxiety.DiscussionAnxiety and depressive symptoms can occur in well-treated young psoriasis patients. Although prevalence is low, their impact may be substantial. These findings indicate the potential importance of targeted psychological screening in this population. Associations with inflammatory and metabolic markers should be considered hypothesis-generating and warrant validation in larger, independent cohorts.